Liquidity Runs - Rafael Matta; Enrico Perotti (Tinbergen Institute, 2016)
Can the risk of losses upon premature liquidation produce bank runs? We show how a unique run equilibrium driven by asset liquidity risk arises even under minimal fundamental risk. To study the role of illiquidity we introduce realistic norms on bank default, such that mandatory stay is triggered before all illiquid assets are sold. Since illiquid assets are not available in a run, asset liquidity risk has a concave effect on run incentives, quite unlike fundamental risk. Runs are rare when asset liquidity is abundant, become more frequent as it falls and decrease again under very low asset liquidity. The socially optimal demandable debt contract limits inessential runs by targeting a high rollover yield. However, the private choice minimizes funding costs, tolerating more frequent runs when illiquid states are sufficiently rare.
Keywords: G21; 330; liquidity risk; bank runs; global games; demandable debt; mandatory stay